THE DISCRIMINATION INDEX AS A PARAMETER FOR THE INTERNAL ANALYSIS OF SIXTY-THREE PSYCHOLOGICAL ITEMS SELECTED FROM STATE EXAMS IN THE DRC. CASE OF THE GOMA FINALISTS. - Matsoro Mitondo Amédée (IJRDO- Journal of Educational Research, 2025)
This article focuses on "the discrimination index as an internal analysis parameter for sixty-three selected psychology items from the DRC State Examinations." We opted to compare the items based on their discriminative values. The formula for calculating the discrimination index was that proposed by Ronald Verbeke. This formula allowed us to identify the following discrimination index categories: - Excellent items - Good items - Average items - Marginal items and items to be eliminated A number of concepts particularly stood out among the most discriminative items, including the concepts of homeostasis, inhibition, céphalo-caudal, reversibility of thought, amnesia, and differential threshold.